EKSTRAKSI KALIUM DARI ABU KULIT BUAH KELAPA (Cocos Nucifera L.) MENGGUNAKAN PELARUT AQUADEST - Gilang Ramadhan, Lilis Sukeksi (Jurnal Teknik Kimia USU, 2018)
In this research, the combustion process was performed conventionally by burning the dried coconut peel of 10 kg in a covered combustion barrel, equipped with a gauge thermometer and having been perforated for the oxygen entrance space for 3 hours with a combustion temperature ranging 500oC and produced ash of coconut peel as much as 1 kg. Extraction was performed by mixing biphasic system between coconut peel ash and aquadest solvent at stirring rate of 250 rpm, variation of time are 40 minutes, 80 minutes, 120 minutes, and 160 minutes with temperatures of 60oC and 80oC. Ash mass ratio: solvent are 5:50, 10:50, 15:50, and 20:50. Results showed that the geater the mass, temperature and extraction time, the higher concentration and pH of alkali extract will be obtained. The concentration and pH of the highest alkali extract were obtained at the ratio of the ash mass: the solvent was 20:50 for the extraction time of 160 minutes at a temperature of 80°C those are 0.775 N and 13.